2016
DOI: 10.1186/s12917-015-0616-1
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized circulation of SAT 1 foot-and-mouth disease virus in cattle herds around Queen Elizabeth National Park in Uganda

Abstract: BackgroundFoot-and-mouth disease (FMD) is endemic in Uganda in spite of the control measures used. Various aspects of the maintenance and circulation of FMD viruses (FMDV) in Uganda are not well understood; these include the role of the African buffalo (Syncerus caffer) as a reservoir for FMDV. To better understand the epidemiology of FMD at the livestock-wildlife-interface, samples were collected from young, unvaccinated cattle from 24 pastoral herds that closely interact with wildlife around Queen Elizabeth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…We demonstrated active circulation of multiple FMDV serotypes in cattle herds across different regions in Uganda during 2014–2017, which is consistent with earlier observations in the region (Mwiine et al, ; Namatovu, Tjørnehøj, et al, ). However, compared with prior reports in Uganda (Ayebazibwe, Mwiine, Tjørnehøj, et al, ; Balinda, Belsham, et al, ; Dhikusooka et al, ; Mwiine et al, ; Namatovu, Belsham, et al, ; Namatovu, Tjørnehøj, et al, ), the results reported here provide new information regarding recent circulation of FMDV in Uganda. We documented the circulation of new genetic lineages in Uganda mostly associated with serotypes O (topotype EA‐1 and EA‐2), SAT 1 (topotype I) and SAT 2 (topotypes VII and X).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…We demonstrated active circulation of multiple FMDV serotypes in cattle herds across different regions in Uganda during 2014–2017, which is consistent with earlier observations in the region (Mwiine et al, ; Namatovu, Tjørnehøj, et al, ). However, compared with prior reports in Uganda (Ayebazibwe, Mwiine, Tjørnehøj, et al, ; Balinda, Belsham, et al, ; Dhikusooka et al, ; Mwiine et al, ; Namatovu, Belsham, et al, ; Namatovu, Tjørnehøj, et al, ), the results reported here provide new information regarding recent circulation of FMDV in Uganda. We documented the circulation of new genetic lineages in Uganda mostly associated with serotypes O (topotype EA‐1 and EA‐2), SAT 1 (topotype I) and SAT 2 (topotypes VII and X).…”
Section: Discussionsupporting
confidence: 71%
“…The percentage of identity within this lineage was 99.7 ± 0.1%, and 99.0 ± 0.4% at the nucleotide and amino acid levels respectively. Interestingly, phylogenetic relationships were found between this lineage and previous viral strains recovered from western Uganda in 1970 (UGA‐Buff/21/70) (Lasecka‐Dykes et al, ) from an African buffalo ( Syncerus caffer ) in the Queen Elizabeth National Park (QENP), and with virus from a cattle herd located near QENP in 1999 (UGA/7/99 and UGA/3/99) (Sahle, Dwarka, Venter, & Vosloo, ) and 2011 (UGA‐116‐13/2011) (Dhikusooka et al, ). Furthermore, phylogenetic analysis classified the vaccine strain T155/71 into topotype I.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Due to its acute, contagious nature, FMDV causes high rates of morbidity, but results in relatively low mortality in adult animals. It is an important disease from an economic perspective due to decreased productivity in food-producing animals, trade restrictions imposed on countries in which the disease is present (Pluimers, Akkerman, van der Wal, Dekker, & Bianchi, 2002;Pomeroy et al, 2015) and animal movement and trade restrictions locally during outbreaks (Dhikusooka et al, 2016). For these reasons, the World Organization for Animal Health (OIE) has developed a framework for the global control and eradication of FMD (OIE and FAO, 2012).…”
Section: Introductionmentioning
confidence: 99%